2009
DOI: 10.1007/s10886-009-9614-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Phenylacetaldehyde-Based Attractant for Common Green Lacewings (Chrysoperla carnea s.l.)

Abstract: In field trapping tests, the catch of Chrysoperla carnea sensu lato (Neuroptera: Chrysopidae) increased when acetic acid was added to lures with phenylacetaldehyde. The addition of methyl salicylate to the binary mixture of phenylacetaldehyde plus acetic acid increased catches even further. The ternary blend proved to be more attractive than beta-caryophyllene, 2-phenylethanol, or 3-methyl eugenol (compounds previously described as attractants for chrysopids) on their own, and no influence on catches was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 38 publications
3
44
1
1
Order By: Relevance
“…Similarly, Jones et al (2010) reported that the attractiveness of iridodial (a maleproduced aggregation pheromone) increased when MeSA was added, doubling the number of lacewings captured in traps in apple orchards. Toth et al (2009) Additionally, the binary combination (MeSA+E(2)H) were not attractive for the predator insect, though we obtained significant results concerning insect attraction to MeSA with Be or F. Our results are also in accordance with some results about the differences in olfactory responses in other predator and parasitoid species to various blends of HIPVs (Simpson et al, 2011;Van Wijk et al, 2011;Maeda et al, 2015). It seems likely that ecological differences may be the cause of such variations in the olfactory responses of different coccinellid species.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Jones et al (2010) reported that the attractiveness of iridodial (a maleproduced aggregation pheromone) increased when MeSA was added, doubling the number of lacewings captured in traps in apple orchards. Toth et al (2009) Additionally, the binary combination (MeSA+E(2)H) were not attractive for the predator insect, though we obtained significant results concerning insect attraction to MeSA with Be or F. Our results are also in accordance with some results about the differences in olfactory responses in other predator and parasitoid species to various blends of HIPVs (Simpson et al, 2011;Van Wijk et al, 2011;Maeda et al, 2015). It seems likely that ecological differences may be the cause of such variations in the olfactory responses of different coccinellid species.…”
Section: Discussionsupporting
confidence: 88%
“…) han sido recolectadas con trampas McPhail utilizando como atrayentes cariofileno, L-triptófano, fenilacetaldehído, iridodial o fosfato amónico+bórax, etc. (Hagen et al, 1976;Canard & Laudého, 1977Canard et al, 1979;Flint et al, 1979;McEwen et al, 1993aBakthavatsalam & Singh, 1996;Ahn et al, 2001;Tóth et al, 2006Tóth et al, , 2009Zhang et al, 2006b;Monserrat, 2008, etc. ) …”
Section: Datos Generales Sobre Su Biología Comportamiento Estadios unclassified
“…Mass production and release of C. pallens in fields is economically unfeasible compared with recruitment of existing individuals in the environment. Based on the feeding habits of adult lacewings, several plant-derived compounds were suggested as attractants [19]–[22]. Recently, individual aphid sex pheromone compounds (enantiomers of nepetalactol and nepetalactone) were shown to attract predatory males of Chrysopa spp.…”
Section: Introductionmentioning
confidence: 99%